2015
DOI: 10.1016/j.scitotenv.2014.11.087
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of polar and nonpolar organic pollutants with soil organic matter: Sorption experiments and molecular dynamics simulation

Abstract: The fate of organic pollutants in the environment is influenced by several factors including the type and strength of their interactions with soil components especially SOM. However, a molecular level answer to the question "How organic pollutants interact with SOM?" is lacking. In order to explore mechanisms of this interaction, we have developed a new SOM model followed by carrying out molecular dynamics (MD) simulations in parallel with sorption experiments. The new SOM model comprises free SOM functional g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 48 publications
(58 reference statements)
3
24
0
Order By: Relevance
“…Generally, nonpolar species will prefer binding in hydrophobic domains and micro(nano) cavities of HSs. Similar observations were recorded by Ahmed et al (2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Generally, nonpolar species will prefer binding in hydrophobic domains and micro(nano) cavities of HSs. Similar observations were recorded by Ahmed et al (2015).…”
Section: Discussionsupporting
confidence: 91%
“…FEP: free energy profile; HS: humic substance; MCPA: 2-methyl-4-chlorophenoxyacetic acid [Color figure can be viewed at wileyonlinelibrary.com] MCPA. A similar trend was observed in the work by Ahmed et al (2015). The authors performed FF-MD simulations to analyze the interactions of nonpolar hexachlorobenzene (HCB) and polar sulphanilamide (SAA) molecules with several models of HSs containing hydrophobic and/or hydrophilic domains.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In recent years, due to the improvement of computer power, MD simulation can be run in a long time and a larger material system 16 . Among them, its application in some special small‐scale geotechnical problems has become a research hotspot 17,18 . It has been used to explore the properties of soil minerals under poor geological conditions, such as expansive soil 19 and frozen soil 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, the sorption technique is most widely used because of its simple operation, low cost, high efficiency, and the fact that it can be applied in large scale in real applications. The elimination of organic pollutants, such as methyl orange, bisphenol A and bisphenol F, dyes, naphthalene, hexachlorobenzene, sulfanilamide, and inorganic pollutants, such as heavy‐metal ions Cr(VI), As(III), Pb(II), Cd(II), and Co(II) and some radionuclides such as 152 + 154 Eu(III), 90 Sr(II), 243 Am(III), 238 U(VI), and 137 Cs(I), using different kinds of natural clay minerals and man‐made nanomaterials has been studied extensively . The results showed that the sorption properties of various pollutants on natural minerals are mainly dominated by the surface properties of the solid particles and the environmental conditions such as pH, ionic strength, temperature, etc.…”
Section: Introductionmentioning
confidence: 99%